ANALISIS TINGKAT KENYAMANAN, KESELAMATAN, DAN KEAMANAN PEJALAN KAKI TERHADAP PEMANFAATAN TROTOAR - Putri (Jurnal Qua Teknika, 2019)
Article entitled "Analysis of Levels of Assessment, Safety and Security of Pedestrians Against Utilization of Sidewalks on Ahmad Yani Street, Blitar City". Sidewalks are a means of transportation for pedestrians to indulge. However, in Blitar City such as Jl. Ahmad Yani is still improving the two terms in terms of physical as well as in terms of utilization. There are still many groups that approve the sidewalk, there is also damage to the sidewalk that makes pedestrians feel uncomfortable for activities. Method of collecting data. Questionnaires and documentation are needed. Analysis of the data used is quantitative data. Data processing using SPSS version 20. The results obtained, the level of comfort (43.95%), safety (52.3%), and security (51.4%) can be categorized quite well.